Geração de perfis climáticos sobre radiação solar e temperatura do ar em Belém do Pará - SILVA, Melchiades Gomes da (2022)
In this study, two different databases are used to perform a statistical treatment on samples of solar radiation and air temperature in the city of Belém-PA comparing the bases and generating final climate profiles for each climate file. Each climate file has a predefined period in relation to its cataloging of climate data, the data expressed in the SWERA climate file are between the years 1973 to 1997, that is, a statistical treatment is carried out over 25 years. In the case of the IWEC climate file, the years analyzed were from 1982 to 1995, so the statistical treatment is carried out over 14 years. The way of compiling climate data from these types of databases requires statistical treatment to enable its use in research that needs a final profile of climate data, as in the case of numerical simulations on thermal performance, or on the feasibility of implantation of photovoltaic energy plants, among other applications. It is noted that the pre-defined objectives in this study were achieved since it was possible to analyze and generate new climate profiles for data on dry bulb, wet bulb, direct solar radiation and diffuse solar radiation between the climate files of the SWERA and IWEC projects.